Impact of malnutrition evaluated by the mini nutritional assessment on the prognosis of acute hospitalized older adults - Kang, Min-gu; Choi, Jung-Yeon; Yoo, Hyun-Jung; Park, Si-Young; Kim, Yoonhee; Kim, Ji Yoon; Kim, Sun-wook; Kim, Cheol-Ho; Kim, Kwang-il (Frontiers in Nutrition, 2023)
Background: Malnutrition is prevalent among hospitalized older patients. Therefore, this study aimed to investigate the association between nutritional status (assessed using the Mini Nutritional Assessment [MNA] and serum albumin levels) and adverse outcomes in hospitalized older patients. We also aimed to compare the predictive utility of our findings. Methods: This retrospective cohort study was conducted between January 2016 and June 2020. In total, 808 older patients (aged ≥ 65 years, mean age 82.8 ± 6.70 years) admitted to the acute geriatric unit were included in our sample. Comprehensive geriatric assessments, including the MNA, were performed. Malnutrition and risk of malnutrition were defined as MNA < 17, albumin < 3.5 g/dL and 17 ≤ MNA ≤ 24, 3.5 g/dL ≤ albumin < 3.9 g/dL, respectively. The primary outcome was that patients could not be discharged to their own homes. The secondary outcomes were overall all-cause mortality, 3-month all-cause mortality, and incidence of geriatric syndrome, including delirium, falls, and newly developed or worsening pressure sores during hospitalization. Results: Poor nutritional status was associated with older age; female sex; admission from the emergency room; high risk of pressure sores and falls; lower physical and cognitive function; higher depressive score; and lower serum albumin, protein, cholesterol, and hemoglobin levels. In the fully adjusted model, malnutrition assessed using the MNA predicted discharge to nursing homes or long-term care hospitals (odds ratio [OR] 5.822, 95% confidence interval [CI]: 2.092–16.199, P = 0.001), geriatric syndrome (OR 2.069, 95% CI: 1.007–4.249, P = 0.048), and 3-month mortality (OR 3.519, 95% CI: 1.254–9.872, P = 0.017). However, malnutrition assessed using albumin levels could only predict 3-month mortality (OR 3.848, 95% CI: 1.465–10.105, P = 0.006). The MNA predicted 3-month mortality with higher precision than serum albumin levels (P = 0.034) when comparing the areas under the receiver operating characteristic curve. Conclusion: Nutritional risk measured by the MNA was an independent predictor of various negative outcomes in hospitalized older patients. Poor nutritional status assessed by serum albumin levels, the most widely used biochemical marker, could predict mortality, but not the development of geriatric syndrome or discharge location reflecting functional status.